Sustainable Human Capacity Development in an Era of Economic Recession : Challenges and Prospects - Fagbemi, Ayodele Omoyiola (Prabandhan: Indian Journal of Management, 2015)
Inadequate human capacity development manifests in both private and public sectors in Nigeria. Apart from large-scale enterprises, especially limited liability companies, systematic capacity development is inadequate in the medium and small-scale enterprises. The aim of this paper is to present ways of achieving sustainable human capacity development in the public and private sectors and to highlight some of the challenges and prospects for the human resource practitioner in ensuring this. The paper proffers the development of a comprehensive human resource management policy for the private and public sectors of Nigeria and the adoption of a systematic approach to training, among other recommendations.